Revealing the Specific Regulations of Brassinolide on Tomato Fruit Chilling Injury by Integrated Multi-Omics - Bai, Chunmei; Zheng, Yanyan; Watkins, Christopher B.; Fu, Anzhen; Ma, Lili; Gao, HongWu; Yuan, Shuzhi; Zheng, Shufang; Gao, Lipu; Wang, Qing; Meng, Demei; Zuo, Jinhua (Frontiers in Nutrition, 2021)
Tomato fruit is susceptible to chilling injury (CI) when stored at low temperatures, limiting its storage potential, and resulting in economic loss if inappropriate temperatures are used. Brassinolide (BR) is a plant growth regulator that is known to decrease the susceptibility of fruit to CI. In this study, transcriptome, metabolome, and proteome analysis revealed the regulation mechanism of BR treatment in alleviating tomato fruit CI. The results showed that the differentially expressed metabolites mainly included amino acids, organic acids, carbohydrates, and lipids. Differentially expressed genes (DEGs) were involved in plant cold stress response (HSFA3, SHSP, and TPR), fruit redox process (POD, PAL, and LOX), related to the fruit texture (CESA, β-Gal, and PAE), plant hormone signal transduction (ACS3, ARF, and ERF,), transcription factors (TCP, bHLH, GATA). Moreover, differentially expressed proteins were associated with fruit texture (CESA, PE, PL, and CHI), plant oxidation processes (LOX, GPX, CAT, and POD), plant cold stress response (HSF, HSP20, HSP70, and HSP90B), plant hormone signal transduction (BSK1 and JAR1) and transcription factors (WRKY and MYB). Our study showed that BR alleviates CI symptoms of tomato fruit by regulating LOX in the α-linolenic acid metabolism pathway, enhancing jasmonic acid-CoA (JA-CoA) synthesis, inhibiting cell wall and membrane lipid damage. The results provided a theoretical basis for further study on the CI mechanism of tomato fruit.